2007
DOI: 10.1002/hyp.6807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growing watershed imperviousness on hydrograph parameters and peak discharge

Abstract: Abstract:An increasing impervious area is quickly extending over the Wu-Tu watershed due to the endless demands of the people. Generally, impervious paving is a major result of urbanization and more recently has had the potential to produce more enormous flood disasters than those of the past. In this study, 40 available rainfall-runoff events were chosen to calibrate the applicable parameters of the models and to determine the relationships between the impervious surfaces and the calibrated parameters. Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 44 publications
(42 reference statements)
0
56
1
1
Order By: Relevance
“…(e.g. Rose and Peters, 2001;Cheng and Wang, 2002;Du et al, 2012;Huang et al, 2008). However, several studies have found mixed effects of urban-ization on peak flows and response times, associated with a combination of imperviousness and flood mitigation measures, especially for basins where urbanization has predominantly taken place after implementation of stormwater control legislation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(e.g. Rose and Peters, 2001;Cheng and Wang, 2002;Du et al, 2012;Huang et al, 2008). However, several studies have found mixed effects of urban-ization on peak flows and response times, associated with a combination of imperviousness and flood mitigation measures, especially for basins where urbanization has predominantly taken place after implementation of stormwater control legislation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the hydrographical characteristics of a developed watershed vary in conjunction with the degree of urbanization (Kliment and Matoušková 2009). Previous studies have shown that the affected factors include rainwater loss (Gremillion et al 2000, Cheng et al 2008b, watershed function (Krug 1996, Kang et al 1998, Aronica and Cannarozzo 2000, Cheng and Wang 2002, surface runoff (Boyd et al 1994, Junil et al 1999, Rodriguez et al 2003, runoff volume (Arnell 1982), peak discharge (Huang et al 2008a(Huang et al , 2008b, time to peak (Huang et al 2012) and baseflow (Simmons and Reynolds 1982). However, the hydrological effects of urbanization may be particularly severe in watershed divisions that are vulnerable to the breaking of links in the hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%
“…(e.g. Rose and Peters, 2001;Cheng and Wang, 2002;Du et al, 2012;Huang et al, 2008). On the other hand, several studies have found mixed effects of urbanisation on flow peaks asso-ciated with a combination of imperviousness and flood mitigation measures, especially for basins in the USA where urbanisation has predominantly taken place after implementation of stormwater legislation to lower peak discharges (e.g.…”
Section: Discussionmentioning
confidence: 99%